Chromatin state origins of uterine leiomyoma - Maritta Räisänen; Eevi Kaasinen; Maija Jäntti; Aurora Taira; Emma Siili; Ralf Bützow; Oskari Heikinheimo; Annukka Pasanen; Auli Karhu; FinnGen; Davide G. Berta; Niko Välimäki; et al. (Nature Communications)
Abstract Aberrations in the regulatory genome play a pivotal role in population-level disease predisposition. Annotation of the regulatory regions using appropriate primary tissues - instead of cell lines affected by selection and other confounding factors - could shed new light into mechanisms underlying common conditions. We test this approach in uterine leiomyomas, highly prevalent benign neoplasms of the myometrium, by creating 15-state chromatin annotations for myometrium and uterine leiomyomas. Integration with RNA-seq, ATAC-seq, HiChIP and methylation data enables us to compare the epigenomes of myometrium and ULs with distinct driver mutations, highlighting the role of bivalent regions in the neoplastic process. Subsequently, a genome wide association study meta-analysis is performed, using three different cohorts. Disease association loci are enriched at active chromatin, especially at enhancers, and harbor tumor- and driver mutation-specific chromatin states. At SATB2 locus we show the effect of the risk genotype already in the normal tissue. Integration of genome-wide association studies and deep regulatory genomics data from the correct tissue type represents a powerful approach in understanding population-level disease predisposition.